Student atlas of world politics - Allen, John L. (McGraw-Hill, 2006)
The Student atlas of World Politics, seventh edition : series combines full-color maps and data sets to introduce students to the importance of the connections between geography and other areas of study such as world politics, environmental issues, and economic development. These thematic atlases will give students a clear picture of the recent agricultural, industrial, demographic, environmental, economic, and political changes in every world region.